THE HEAT TRANSFER FLOW ANALYSIS OF THE JIS G 3106 SM520B STEEL PLATE CUTTING PROCESS USING CNC FLAME CUTTING MACHINE IN THE MANUFACTURE OF THE BOTTOM PLATE BOX GIRDER - Puspawan, Angky; Febriansyah, Febriansyah; Suandi, Agus; Supardi, Nuruliman (Rekayasa Mekanika: Jurnal Ilmiah Teknik Mesin, 2021)
PT. XYZ uses CNC flame cutting technology to produce steel bridge material with the principle of thermal cutting which will cause the phenomenon of heat transfer and heat affected areas. By using the inverse method to determine the application of heat on the SM520B steel plate. The JIS G3106 SM520B steel plate is formed from a Heat Affected Area (HAZ). This happens because of differences in cutting temperature and the temperature of the Steel Plate. The analysis results obtained from conformity with the Box Girder design. In the Box Girder design, the active load is given a distance of 60 mm from the heat- area affected so as not to fatigue.